Imaterialidade do Patrimônio e Identidade Social: uma análise da lei Robin Hood de Minas Gerais - Campos, Yussef Daibert Salomão de (2010)
The dissertation studies the relationship between social identity and cultural property, especially the intangible heritage one. This is carried out through the study of specific legislation, focusing on the Robin Hood Act, Minas Gerais, which deals with the transfer of state tax to municipalities that provide attention to their cultural property. The main objective of this study is highlight the social identity as a legitimizing protection of cultural heritage in all its categories and demonstrate that we should not build a pyramid hierarchy between the categories of cultural heritage, and more: that national identity is formed by a myriad of local identities, understood as concepts constructed from conflicts and disputes between these identities, which result in certain political practices. In addition, the study analyses how the law acts constructs imagined communities. This can be seen from the analysis of relevant legislation, as well as in comparison to Brazilian legislation, in particular the mining and the law of "Ciudad Autonoma de Buenos Aires", Argentina. Through this study will be seen that cultural heritage is a field of conflict between identities, and that the public practice in this area are a reflection of this standoff